Literature's sensuous geographies : postcolonial matters of place - Moslund, Sten Pultz (Geocriticism and spatial literary studies., 2015)
"Literature's Sensuous Geographies offers a study of place in postcolonial literature and theory from other than the socio-cultural and political angles that have traditionally dominated the field. Moslund explores "sensuous geographies" (something that has so far been neglected in the study of place in literature) as opening up other than discursive relations to the world - other, non-territorial modes of being-in-the-world. The book develops a sense-aesthetic mode of reading (a "topo-poetics") and in close-readings of Conrad, Blixen, Coetzee and Achebe (among others), Moslund explores dimensions in literature that open up the place world as produced by desubjectified intensities of smell, sound, sight, touch, etc. Sense-aesthetic qualities of literary language are shown in this way as radically challenging the rationalizing logic of modernity (the inner logic of imperialism), at the heart of which Moslund identifies a disciplining of the senses and a reduction of the sensuous openness of reality. With his study of sensuous geographies in literature, Moslund makes a notable shift in the field of postcolonial studies and geocriticism from discourse analysis to aesthetic analysis"--